2008
DOI: 10.1111/j.1469-7580.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of the forelimb in arboreal frogs: specializations for grasping ability?

Abstract: Frogs are characterized by a unique morphology associated with their saltatory lifestyle. Although variation in the form and function of the pelvic girdle and associated appendicular system related to specialized locomotor modes such as swimming or burrowing has been documented, the forelimbs have typically been viewed as relatively unspecialized. Yet, previous authors have noted versatility in forelimb function among arboreal frogs associated with feeding. Here we study the morphology and function of the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
144
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(163 citation statements)
references
References 29 publications
4
144
1
14
Order By: Relevance
“…Although there exists a voluminous literature on grip force in the fields of kinesiology and physical anthropology, studies in non-primate vertebrates lag considerably behind those of bite force. Studies of grip force in some frogs (Manzano et al, 2008) and lizards (Abdala et al, 2009) have revealed insights into the role of gripping for arboreal locomotion, along with myological and physiological specializations for enhancing grip forces. The few published studies of in vivo grip force in raptorial birds have contributed substantially, by revealing mechanisms of prey capture and killing, and their implications for foraging behavior and ecology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although there exists a voluminous literature on grip force in the fields of kinesiology and physical anthropology, studies in non-primate vertebrates lag considerably behind those of bite force. Studies of grip force in some frogs (Manzano et al, 2008) and lizards (Abdala et al, 2009) have revealed insights into the role of gripping for arboreal locomotion, along with myological and physiological specializations for enhancing grip forces. The few published studies of in vivo grip force in raptorial birds have contributed substantially, by revealing mechanisms of prey capture and killing, and their implications for foraging behavior and ecology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are many arboreal frogs around the world, including most of the hylids, centrolenids, rhacophorids and hyperolids (Manzano et al, 2008). There are many arboreal frogs around the world, including most of the hylids, centrolenids, rhacophorids and hyperolids (Manzano et al, 2008).…”
mentioning
confidence: 99%
“…Ability to perform these complex movements is interpreted as an significant factor for the specialization of the forelimbs for locomotion. [1] Grays et al in 1997 described that adduction of the thumb towards the digits such that the palmar surfaces of the thumb and digit touch each other is required for a precision grip. Precision grip is thought to be used during locomotion and in the manipulation of some food items.…”
Section: Introductionmentioning
confidence: 99%